Penerapan Intervensi Manajemen Halusinasi Dalam Mengurangi Gejala Halusinasi Pendengaran - Ari Yoga; Darjati; Ita Apriliani (AKPER Pasar Rebo, 2022)
Abstract Schizophrenia is often characterized by the appearance of auditory hallucinations. Uncontrolled hallucinations will make the client hysterical, weak, and violent acts appear. This study aims to determine the appropriate intervention to be given to patients who experience auditory hallucinations. This research is a case study type with simple random sampling technique for determining respondents. The study was conducted in February 2022 using a hallucination assessment format instrument. The nursing care process starts from the assessment process to evaluation. Complaints felt by clients are feelings of wanting to get angry when they hear whispers and often talk to themselves. Whispering sounds like the sound of a fight, a voice that invites to do evil to a voice that always scolds him. The administration of hallucinatory management intervention carried out for 3 days showed the results that were able to overcome the nursing problem of sensory perception disorders partially resolved. Seen from the condition of the client who is calmer and can control the hallucinations that are felt. The recommendation of this study is that nurses can apply hallucinations as well as modified with other group activity therapy.